The Buckingham’s π Theorem: Consequences for the Price Theory - GANCHEV, Gancho Todorov (Journal of Mathematical Economics and Finance; Vol 9 No 1 (2023): JMEF, Volume IX, Issue 1(16), Summer 2023DO - 10.14505/jmef.v9.1(16).02, 2023)
The present article focuses on the possible interpretation of the pi theorem of physics in the field of the economics' general equilibrium analysis. The physical units of the exchanged goods are de ned as fundamental units and the neoclassical prices as dimensionless derived numbers. Thus, the general equilibrium does not need money metrics, unspeci ed money market and the complementing inappropriate incorporation of the Walras Law. Further, the main function of money is not that of a unit of account, but a means of exchange. If such type of a money market is introduced, the Walras symmetry holds but in the sense that the positive aggregate excess demand on the goods market matches the negative excess demand on the money market. Distinction is de ned between neoclassical, relative and monetary prices. Additional conditions must be met to allow for a closed monetary circulation.